Burundi : Third Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report ;, 2013)
This paper analyzes Burundi's Third Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria. Policy discussions in the program focus on measures to strengthen fiscal performance, which have been reflected in a revised 2013 budget, bolstering public financial and debt management. The report highlights that the macroeconomic outlook remains difficult, compounded by downside risks related to uncertainties in the external economic environment. Also, the need to preserve debt sustainability continues to anchor medium-term fiscal policy.